Mapas mentales y expresión oral del inglés en los estudiantes de idiomas de la Universidad Nacional de Trujillo, 2020 - Diaz Linares, Rosa Xiomara (2022)
The present thesis "Mind maps and oral expression of the English language" aimed to determine the influence of the didactic strategy of mind maps and in the oral expression of the English language in the students of II cycle of Languages of the National University of Trujillo._x000D_ The sample consisted of 20 university students, in the same way, we worked with a pre- experimental design oriented to a single group, applying a pre-test and a post-test that allowedus to collect data, using the rubric as an evaluation instrument for oral production in the English language. The results product of the application of the didactic strategy of mind mapsshowed that in the group were an improvement of 25%, placing the student at the “very good”level of oral expression of the English language._x000D_ It was finally concluded that the didactic strategy of mind maps has a positive influence on the oral expression of the English language in the students of the II cycle of languages of theNational University of Trujillo.